Typification of the name Senecio pygmaeus (Asteraceae), with some additional taxonomic and phytogeographic remarks - Pasta, Salvatore; Jeanmonod, Daniel; Troia, Angelo (Mediterranean Botany, 2022)
A thorough research on the scientific activity of Guglielmo Gasparrini, Giovanni Gussone and Augustin Pyramus De Candolle allowed the authors to adress a research in several European herbaria looking for the type of the name Senecio pygmaeus DC. The original specimen sent by Gussone and mentioned in the protologue by Candolle is still kept at G-DC and is designated as the lectotype, whilst three other herbarium sheets, preserved at NAP-GUSS, PAL and PAV herbaria respectively, in all probability belong to the same gathering, and are considered as isolectotypes. The authors provide an updated description of this taxon in order to better point out its diagnostic characters. However, further biosystematic and phytogeographic surveys are needed to ascertain the taxonomic value and the distribution range of S. pygmaeus. Indeed, it might represent just a dwarfed, salt-tolerant ecotype of S. leucanthemifolius Poir. or S. vulgaris L., hence be more widespread than previously reported, counting numerous scattered populations along the rocky shores of central and eastern Mediterranean countries.